Validation of time domain seakeeping computations based on capsizing model tests in natural seaways - Büsken, Wiebke; Krüger, Stefan; Russell, Philipp; Frühling, Christian (2022)
This paper presents further validation of the numerical computation method E4ROLLS, a nonlinear potential flow theory based seakeeping code, which is especially suitable for the early design stage due to its fast and efficient computation. The validation is achieved by comparison of simulation results with historical capsizing model test results of free-running self-propelled ship models in natural seaways. The results show that E4ROLLS is well-suited to assess the ships’ capsizing vulnerability, especially in following seas. Analysis of the historical tests’ video footage shows that the models’ capsizing in head seas was mainly induced by gusty wind. E4ROLLS is extended to include heeling moments caused by changing wind speeds and directions, so that wind-induced capsizing behavior can also be anticipated. The presented work highlights the benefits of model-scale seakeeping tests in natural seaways and shows that it is possible to assess the seakeeping of ships with fast and reliable methods in the early design stage.